The Fekete-Szegö Problem for p-Valently Janowski Starlike and Convex Functions - Toshio Hayami; Shigeyoshi Owa (International Journal of Mathematics and Mathematical Sciences)
For p-valently Janowski starlike and convex functions defined by applying subordination for the generalized Janowski function, the sharp upper bounds of a functional |ap+2−μa2p+1| related to the Fekete-Szegö problem are given.